Experimental Vapor-Liquid Equilibrium Data for Binary Mixtures of Methyldiethanolamine in Water and Ethylene Glycol under Vacuum - Soames, A.; Al Helal, A.; Iglauer, Stefan; Barifcani, Ahmed; Gubner, Rolf (American Chemical Society, 2018)
© 2018 American Chemical Society. Methyldiethanolamine (MDEA) is a widely used chemical in the natural gas processing industry as a solvent for CO2and H2S capture and as a basic compound for pH stabilization corrosion control. During pH stabilization corrosion control, the removal of MDEA during the (mono)ethylene glycol (MEG) regeneration process may occur under vacuum conditions during reclamation in which the removal of salt cations is performed. Isobaric vapor-liquid equilibrium data for the binary MEG-MDEA system is presented at (20, 10 and 5) kPa and water-MDEA system at (40, 20, 10) kPa to simulate its behavior during MEG reclamation under vacuum. Vapor and liquid equilibrium concentrations of MDEA were measured using a combination of ion chromatography and refractive index. The generated experimental VLE data were correlated to the UNIQUAC, NRTL, and Wilson activity coefficient models, and the respective binary parameters were regressed.